Kecerdasan Buatan Mengurangi atau Meningkatkan Beban Kerja Gen Z di Bidang Akuntansi? - Thomas Aquinas Wijanarko; Sofian; Natalia Kristina (Jurnal Literasi Akuntansi, 2026)
The main focus of this research is to examine how perceived usefulness and ease of use of AI, as well as the alignment of socio-technical aspects, influence individuals’ perception of workload in the application of AI. This study employs Structural Equation Modeling (SEM) with LISREL to analyze the relationships between technology acceptance, socio-technical support, and workload in AI usage. The data were collected from Generation Z employees working in the accounting field, in order to capture their perceptions of usefulness, socio-technical alignment, and organizational support in the implementation of AI in their professional tasks. The findings reveal that the higher the acceptance of AI, the higher the perceived workload from Gen Z employees. Furthermore, this study found that the socio-technical system provided by the organization does not necessarily simplify the work of Gen Z employees in the accounting field. Future research should consider stratified sampling to examine contextual differences. This study highlights the necessity of simplifying socio-technical processes so that organizational support does not create new complexities in the implementation of AI in accounting. This research underscores the importance of balancing individual technology acceptance and organizational socio-technical system design, ensuring that AI implementation addresses not only technical aspects but also maintains employee well-being, motivation, and social relationships within the workplace. This study provides novelty by offering a perspective on AI adoption among Generation Z accounting employees through the integration of technology acceptance and socio-technical system to explain workload perceptions. The findings are expected to enrich the literature on technology adoption, particularly artificial intelligence, in the accounting profession.